Towards Moral Media: Christian Perspectives on the Evolving Landscape of Mass Communication in Light of Jubilee 2025 - Paul Rohan, J.C. (Third Millenium, Gujarat, India, 2025)
The global media landscape is undergoing a period of profound transformation, characterized by rapid technological advancements and pervasive digital interconnectivity. While contemporary mass communication offers unprecedented opportunities for reach and influence, it is increasingly challenged by ethical crises, including the proliferation of misinformation, societal polarization, sensationalism, and a decline in public trust. This paper investigates the intersection of Christian ethics, public theology, and digital media, proposing a framework for morally responsible communication practices informed by the core themes of the Roman Catholic Church’s Jubilee Year 2025. Anchored in the scriptural and theological vision of Jubilee, understood as a time of renewal, reconciliation, and the cultivation of hope, this study applies Christian moral thought to address the pressing ethical dilemmas confronting mass communication today. Employing a multidisciplinary methodology that integrates theological analysis and comparative ethical critique, the research draws upon Church teachings, papal pronouncements, and observed media practices to construct a theologically grounded and practically applicable model of moral media engagement. Particular attention is devoted to the ethical implications of emerging digital trends, such as artificial intelligence, algorithmic influence, deep-fakes, and the evolving dynamics of influencer culture. Through a critical analysis of some Christian media initiatives, this paper examines the extent to which faith-based communication endeavours reflect - or fail to reflect - Christian values of truth, human dignity, and service to marginalized communities. Ultimately, the study advocates for a Jubilee-inspired renewal of media culture, one that prioritizes the restoration of trust, fosters constructive dialogue, and re- envisions communication as a vocation of hope. It concludes by articulating concrete ethical guidelines for communicators and outlining pathways for pastoral, academic, and institutional engagement aimed at fostering a more humane, morally grounded, and socially responsible media environment.
Keywords: Moral Media; Ethical Imperative; Jubilee; Misinformation; Disinformation